Knowledge management system SOP using semantic networks connected with personnel information system: case study Universitas Singaperbangsa Karawang - Intan Purnamasari; Irman Hermadi; Yani Nurhadryani (Universitas Ahmad Dahlan, 2019)
Document Standard Operating Procedures (SOP) can manage business processes and employee performance in an organization. This study aims to develop a system that can publish SOP documents automatically distributed to employees. In this study, an analysis of the relationship between SOP documents and employees is carried out so that it can be directly allocated to employees according to the position. Knowledge analysis of the relationship between SOP documents and employees is done using semantic network analysis. Semantic networks are used to analyze components of knowledge and the relationship between SOP documents and employees. The results of the report of the elements of knowledge and the relationship between SOP documents found 25 SOP documents were consisting of 6 types of central nodes with 156 child nodes and had 7 types of relations containing 207 relations. SOP knowledge management system is connected to the personnel information system (SIPEG) so that it makes it easier for users to find, accommodate, and manage the knowledge contained in SOP documents. System implementation is done using PHP programming language with CodeIgniter framework, Rest API, and MySQL database.